An Approach of Developing Floating Tablet of Lisinopril - Jain, Nidhi; Gupta, Rahul (Current Research in Pharmaceutical Sciences, 2016)
Lisinopril is an antihypertensive agent with 12 hr half life, pH-dependent solubility, and narrow absorption window. So, the present study aimed to prolong its gastric residence time that entailed a development of an optimized gastro retentive floating tablets (GRFTs). The tablets were fabricated by direct compression using hydroxypropyl methylcellulose and carbopol 934 as release retarding polymers. The quality attributes of the tablets were evaluated. The buoyancy lag time, total floating time, swelling ability and in vitro release studies were al so carried out in 0.1 N HCl (pH 1.2) at 37 ± 0.5 °C. Statistical data analysis revealed that the optimized formulation containing 21.91% HPMC and 15% carbopol 934 had acceptable hardness, optimum floating behavior and 24h controlled-release pattern. The design succeeded to develop CVD-GRFTs with floating ability and controlled release behavior that could improve its solubility, and improve its availability at the best absorptive site.